2016
DOI: 10.1371/journal.pgen.1006462
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Expression of the Drosophila eyes absent Gene Is Controlled by Several Cooperatively Acting Cis-regulatory Elements

Abstract: The eyes absent (eya) gene of the fruit fly, Drosophila melanogaster, is a member of an evolutionarily conserved gene regulatory network that controls eye formation in all seeing animals. The loss of eya leads to the complete elimination of the compound eye while forced expression of eya in non-retinal tissues is sufficient to induce ectopic eye formation. Within the developing retina eya is expressed in a dynamic pattern and is involved in tissue specification/determination, cell proliferation, apoptosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 53 publications
(93 reference statements)
1
28
0
Order By: Relevance
“…In support of this model, a developmental analysis of so and eya mutants demonstrated that several nonocular selector genes, which are not normally expressed within the eye, are de‐repressed within the retinal progenitor cells and this leads to a homeotic transformation of the eye into head epidermis (Fig. ) (Salzer and Kumar, ; Wang and Sun, ; Weasner and Kumar, ; Weasner et al, ). The eye can also be transformed into an antenna by alterations in the EGF Receptor and Notch signaling pathways (Fig.…”
Section: Tissue Fate Specification: When the Best Offense Is A Good Dmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of this model, a developmental analysis of so and eya mutants demonstrated that several nonocular selector genes, which are not normally expressed within the eye, are de‐repressed within the retinal progenitor cells and this leads to a homeotic transformation of the eye into head epidermis (Fig. ) (Salzer and Kumar, ; Wang and Sun, ; Weasner and Kumar, ; Weasner et al, ). The eye can also be transformed into an antenna by alterations in the EGF Receptor and Notch signaling pathways (Fig.…”
Section: Tissue Fate Specification: When the Best Offense Is A Good Dmentioning
confidence: 94%
“…Although these mutants have been around for decades, a century in the case of ey alleles, it had been widely assumed that the surrounding head epidermis overgrows to compensate for the loss of the entire field of retinal progenitors. Indeed, relatively high levels of cell death are observed in both so and eya mutants making the over‐proliferation/compensation model perfectly reasonable and parsimonious (Bonini et al, ; Weasner and Kumar, ; Weasner et al, ).…”
Section: Tissue Fate Specification: When the Best Offense Is A Good Dmentioning
confidence: 99%
“…We next set out to determine if the underlying cause of the headless phenotype or the disappearance of double knockdown clones is activation of apoptosis because elevated cell death levels are observed when other retinal determination genes are removed (16,59,60). To examine apoptosis in the developing eye-antennal disc, we induced the loss of Ey/Toy using the tub-GAL80[ts]/DE-GAL4 system.…”
Section: Ey and Toy Proteins Are Essential For Survival And Proliferamentioning
confidence: 99%
“…To understand the mechanism by which Ey and Toy promote early eye-antennal disc proliferation, we turned our attention to retinal determination genes that are known to promote progenitor cell survival and proliferation in the eye-antennal disc. Eya, as part of the So-Eya complex, is sufficient to promote cell proliferation and inhibit cell death (16,59,60,69,70); however, it is not activated until the second-larval instar, and its expression is limited to the eye field. On the other hand, eyg and tsh initiate expression during embryogenesis and the first-larval instar, respectively (12,(34)(35)(36)71).…”
Section: Ey and Toy Regulate Eye-antennal Disc Proliferation Through mentioning
confidence: 99%
“…During Drosophila eye development, the gene eyes-absent (eya) is expressed in undifferentiated cells that undergo cell division, as well as in differentiating cells that do not divide anymore. Although these cells are present in the same tissue in close proximity, the expression of eya is regulated by different combinations of several enhancers [81]. The modularity and dynamic usage of enhancers have also been shown on a genome-wide scale during Drosophila embryonic development [82].…”
Section: Transcriptional Regulation -Transcription Factors and Cis-rementioning
confidence: 99%